Analysis Of Forming Limit Diagrams In Aluminum Sheet Alloy by Universal Tensile Testing - ADRI, MUHAMMAD LOKMAN; DR Ng Chuan Huat (Research Progress in Mechanical and Manufacturing Engineering, 2022)
The increase of the demand in strengthening the material in over the years made many researchers and new technology and methods in hot press forming introduced. The heating process have potential to increase the strengthening material. In this study, the experimental method by conducted the tensile testing was made to study the effect of elevated heating temperature toward tensile testing result. The aluminium alloy AA6061 and AA7075 was selected as the material on this study. The experiment starts with workpiece preparation and then heated in furnace with different several temperatures. After that, the specimen moves to tensile testing process with tension test was applied. The result was obtained in load force-elongation graph and stress-strain graph was discussed and compared with the previous studies. Based on the previous study, the heating temperature increase effect the increase of load force and stress. The objective of this study was achieved.